The Effect of Citicoline Injections on Children with Organic Brain Syndrome Caused by Infection - Endang Warsiki (Indonesian Pediatric Society, 1993)
Forty children with organic brain syndrome caused by injections were given Citicoline intramuscular injections. Twenty of these children were within 3 months postencephalitis, the other 20 children were over 3 months postencephalitis. There were statistically significant negative correlations between the length of time from recovery from encephalitis to the initiation of administration of CDP choline and the improvement of many of the symptoms of OJ'8anic brain syndrome. In other words, these patients who began receiving Citicoline (CDP choline) within 3 months showed greater improvement than those who began receiving CDP choline over 3 months after recoveries from encephalitis.